2020
DOI: 10.1111/1365-2745.13535
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mapping of root systems reveals diverse strategies of soil exploration and resource contest in grassland plants

Abstract: When foraging and competing for below‐ground resources, plants have to coordinate the behaviour of thousands of root tips in a manner similar to that of eusocial animal colonies. While well described in animals, we know little about the spatial behaviour of plants, particularly at the level of individual roots. Here, we employed statistical methods previously used to describe animal ranging behaviour to examine root system overlap and the efficiency of root positioning in eight grassland species grown in monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 65 publications
(91 reference statements)
3
19
0
Order By: Relevance
“…a distance-related cost of nutrient transport from soil location to plant stem) is incorporated in Gersani et al ’s original model, the new model predicts that plants should overproduce (or underproduce) roots in nutrient patches that are closer to (or further away from) them than to neighbours, due to a relative lower (or higher) cost of nutrient transportation in shorter (or longer) distance than neighbours. This prediction appears to be supported by some empirical observations ( Cabal et al 2020 ; Lepik et al 2021 ). Their findings indicate that interplant distance (or plant density) is a critical component determining root foraging behaviours of plants in resource competition ( Cabal et al 2020 ), and suggest that an evaluation of root production at whole-plant level or over large spatial scales may lead to incomplete- even miss-understanding of plant–plant root interaction ( Semchenko 2020 ).…”
Section: Discussionsupporting
confidence: 79%
“…a distance-related cost of nutrient transport from soil location to plant stem) is incorporated in Gersani et al ’s original model, the new model predicts that plants should overproduce (or underproduce) roots in nutrient patches that are closer to (or further away from) them than to neighbours, due to a relative lower (or higher) cost of nutrient transportation in shorter (or longer) distance than neighbours. This prediction appears to be supported by some empirical observations ( Cabal et al 2020 ; Lepik et al 2021 ). Their findings indicate that interplant distance (or plant density) is a critical component determining root foraging behaviours of plants in resource competition ( Cabal et al 2020 ), and suggest that an evaluation of root production at whole-plant level or over large spatial scales may lead to incomplete- even miss-understanding of plant–plant root interaction ( Semchenko 2020 ).…”
Section: Discussionsupporting
confidence: 79%
“…Instead, we believe that plastic and species-specific root responses to plant order of arrival are more likely to explain why grasses-first communities rooted more shallowly than the others did. Such plastic root responses affecting root allocation and foraging have been well documented in the past (Mahall and Callaway, 1991;Semchenko et al, 2007;Mommer et al, 2012;Kumar et al, 2020;Lepik et al, 2021) but, to date, there has been little evidence that the order of arrival of plants can affect the root distribution of individual species (Weidlich et al, 2018a). Studying the extent to which the behaviour of the roots of species inhabiting plant communities changes as a function of the order of arrival of plants, as well as studying how these plastic root responses would be reflected at the community level, requires information on the distribution of roots at the species level, which unfortunately was not available in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Although strong differences in root distribution exist between individual plant species (Herben et al, 2018;Lepik et al, 2021), evidence for differences in root distribution between plant functional groups in grassland ecosystems has been mixed, with some studies reporting no difference in rooting depth between functional groups (Mommer et al, 2010;Ravenek et al, 2014;Oram et al, 2018), while others have indicated that forb species root deeper on average than grasses (Bakker et al, 2019;Chen et al, 2020). Since our plant communities had exactly the same species and functional group composition and only differed by the order of arrival of forbs, grasses and legumes, differences in rooting depth between species or functional groups is unlikely to be the only explanation behind our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the positive effect may disappear at the later growing stage of plants when the soil-sand ratio was modified by these plants during the growing stages (Roiloa and Retuerto, 2006;Dong et al, 2015). Moreover, such an effect may disappear in a population or community since some individuals in this population or community could detect the neighbors and avoid direct competition (Novoplansky, 2009;Lepik et al, 2021), and some other individuals may perform in the opposite direction. The result depends on the combination of these two effects.…”
Section: Discussionmentioning
confidence: 99%